Unusual presentation of gallbladder perforation. (2016) - Jayasinghe, G.; Adam, J.; Abdul-Aal, Y.
Highlights: Percutaneous abscesses arising from the gallbladder are a rare but potentially serious consequence of acute cholecystitis, and may present in a wide variety of locations. Silent cholecystitis is a rare but significant cause of sepsis. It is imperative to conduct a full body inspection in the septic patient, even when a source has been identified. Early surgical intervention is invaluable in suspected abscesses, regardless of the availability of pre-operative imaging. Abstract: Introduction: Gall bladder perforation is associated with high mortality rates and therefore must be recognised and managed promptly. We present an unusual presentation of spontaneous gall bladder perforation. Case presentation: An elderly lady with multiple medical co-morbidities was admitted with sepsis following a fall. Initial assessment lead to a diagnosis of pneumonia, however a rapidly expanding right flank mass was incidentally noted during routine nursing care. Imaging studies were inconclusive, however incision and drainage of the mass revealed bile stained pus draining cutaneously from an acutely inflamed gallbladder. The patient made a good recovery following surgery, and was discharged with outpatient follow-up. Discussion: Despite focussed post-hoc history taking she denied any prodromal symptoms of cholecystitis. In addition to reporting an unusual cause for a common presentation, we highlight the importance of a full body examination in the context of sepsis, regardless of whether the source has been identified. In addition, we advocate that surgical intervention in sepsis should not be delayed by imaging in cases where an abscess is suspected. Conclusions: Percutaneous abscesses arising from the gallbladder are a rare but potentially serious consequence of acute cholecystitis, and may present in a wide variety of locations. Therefore it is imperative to conduct a full body inspection in the septic patient, even when a source has been identified.